Preparation and In Vitro/In Vivo Evaluation of Orally Disintegrating/Modified-Release Praziquantel Tablets - Xuemei Wen; Zhaoyou Deng; Yangfeng Xu; Guoqing Yan; Xin Deng; Liqin Wu; Qiuling Liang; Fang Fang; Xin Feng; Meiling Yu; Jiakang He (MDPI AG, 2021)
This study was designed to develop orally disintegrating/sustained-release praziquantel (PZQ) tablets using the hot-melt extrusion (HME) technique and direct compression, and subsequently evaluate their release in in vitro and in vivo pharmacokinetics. For the extrusion process, hypromellose acetate succinate (HPMCAS)-LG was the carrier of pure PZQ, with a standard screw configuration used at an extrusion temperature of 140 °C and a screw rotation speed of 100 rpm. Differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), powder X-ray diffraction (PXRD) and Fourier-transform infrared spectroscopy (FTIR) were performed to characterize the extrudate. Orally disintegrating/sustained-release praziquantel tablets (PZQ ODSRTs) were prepared by direct compression after appropriate excipients were blended with the extrudate. The release amount was 5.10% in pH 1.0 hydrochloric acid at 2 h and over 90% in phosphoric acid buffer at 45 min, indicating the enteric-coating character of PZQ ODSRTs. Compared with the pharmacokinetics of marketed PZQ tablets (Aipuruike®) in dogs, the times to peak (Tmax), elimination half-life (t1/2λ) and mean residence time (MRT) were extended in PZQ ODSRTs, and the relative bioavailability of PZQ ODSRTs was up to 184.48% of that of Aipuruike®. This study suggested that PZQ ODSRTs may have potential for the clinical treatment of parasitosis.